2020
DOI: 10.3390/ma13235437
|View full text |Cite
|
Sign up to set email alerts
|

AI-Optimized Technological Aspects of the Material Used in 3D Printing Processes for Selected Medical Applications

Abstract: While the intensity, complexity, and specificity of robotic exercise may be supported by patient-tailored three-dimensional (3D)-printed solutions, their performance can still be compromised by non-optimal combinations of technological parameters and material features. The main focus of this paper was the computational optimization of the 3D-printing process in terms of features and material selection in order to achieve the maximum tensile force of a hand exoskeleton component, based on artificial neural netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 42 publications
0
36
0
1
Order By: Relevance
“…The individual hand geometry produced without the need of complex scanning devices serve as effective design references for improving hand products, especially during the COVID-19 pandemic seriously. On the other hand, PLA indeed provided more supporting constraint satisfaction for reaching more tensile force due to the character of the hardness according to the past research in materials [21] [22]. However, the questionnaire indicated that PLA has less satisfaction than other materials because the splint made by PLA is too hard to wear.…”
Section: Questionnaire Integrationmentioning
confidence: 83%
“…The individual hand geometry produced without the need of complex scanning devices serve as effective design references for improving hand products, especially during the COVID-19 pandemic seriously. On the other hand, PLA indeed provided more supporting constraint satisfaction for reaching more tensile force due to the character of the hardness according to the past research in materials [21] [22]. However, the questionnaire indicated that PLA has less satisfaction than other materials because the splint made by PLA is too hard to wear.…”
Section: Questionnaire Integrationmentioning
confidence: 83%
“…It seems that both the optimization of the use of materials itself and its widespread application should become obligatory practice. However, this requires not only public and business awareness, but also legal regulations as part of a sensible strategy for entire countries, and in the initial period of use as well as incentives in the form of tax breaks and building an image of resource-efficient companies [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The selection of appropriate materials is very important for the target effect of shaping elements using RP techniques. These issues were described by Leturia et al [ 25 ], as well as Rojek et al [ 26 ].…”
Section: Methodsmentioning
confidence: 95%